Pakistan Development Update, October 2018 : At A Crossroad - World Bank (World Bank, Washington, DC, 2018)
The objective of this report is to update the Government of Pakistan, think-tanks and researchers, the public and the World Bank’s senior management on the state of the Pakistan economy and its outlook, together with the structural reforms it requires and the development challenges it faces. The report begins with a chapter on economic developments, with sections on growth, fiscal policy, public debt, the external sector, monetary developments and inflation, and the financial sector. The second chapter provides a medium-term macroeconomic outlook and describes risks faced and upcoming challenges, including structural reform needs. The third chapter concludes by stressing the importance of creating a skilled labor force that is more productive and better able to adopt and adapt to new technologies—the core of Pakistan’s growth path.